2022
DOI: 10.3389/fpsyg.2021.763658
|View full text |Cite
|
Sign up to set email alerts
|

Unofficial Media, Government Trust, and System Confidence Evidence From China: An Empirical Exploration of the Attitudes of Netizens Based on the Dual Moderating Effect

Abstract: Mass media has a significant impact on public support for the government. This manuscript constructs a mixed model with official media use as the moderating variable and government trust as the intermediary variable to explore the mechanism of how unofficial media use affects system confidence, using data from a survey of the political and social attitudes of netizens (2015). The study finds that official media use weakens the negative role of unofficial media use in building system confidence, with the interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…The questionnaire asked participants if they frequently receive political news and current affairs commentary from different channels, including CCTV, Xinhua News Agency, Sina, and other media outlets, with response options ranging from 1 (almost never) to 5 (more than one hour per day). Results from principal component factor analysis revealed two common factors, named ‘unofficial media use’ and ‘official media use’, which is consistent with previous research by Wang and Jin [ 63 ] and Chen et al [ 42 ]. Unofficial media use includes platforms such as Weibo or online communities, WeChat, grapevine or chatting with friends, and overseas media.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The questionnaire asked participants if they frequently receive political news and current affairs commentary from different channels, including CCTV, Xinhua News Agency, Sina, and other media outlets, with response options ranging from 1 (almost never) to 5 (more than one hour per day). Results from principal component factor analysis revealed two common factors, named ‘unofficial media use’ and ‘official media use’, which is consistent with previous research by Wang and Jin [ 63 ] and Chen et al [ 42 ]. Unofficial media use includes platforms such as Weibo or online communities, WeChat, grapevine or chatting with friends, and overseas media.…”
Section: Methodssupporting
confidence: 89%
“…Scholars have observed that unofficial media use can undermine political trust [ 35 , 42 , 43 ]. Public’s demand for diversified information acquisition and official media’s silence on political scandals, environmental pollution, social injustice and other issues prompt the public to seek unofficial media as information sources [ 7 ].…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
“…On the one hand, in the perspective of "uses and gratification," official media exposure as a positive information acquisition behavior generates positive psychological experiences (Choi and Choung, 2021). On the other hand, considering the information contents, these findings once again validate the positive role of official media primarily expresses the will of the government can significantly improve public perception of the government (Song and Lee, 2016;Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 64%
“…TV channels and newspapers) and new media (e.g. official accounts on social media platforms) (Chen et al ., 2022). Through official media, the public sector with the government as the core can release news, provide useful information and interact with the public while simultaneously setting the agenda and structuring the news in a way that serves the ruling party interests (Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Brazil and Mexico, it was shown that those who were more engaged in political discussion on social media were more likely to show distrust towards government authority (Araguete et al, 2021). When observing those who receive more of their news from social online communities, studies showed an increase in critical attitudes towards those in power, leading to a negative perception of those in the current political system (Chen et al, 2022). Social media was devised to lead to greater transparency in communication and more trust between members of society.…”
Section: Social Media's Role In Eroding Public Trust In Governmentmentioning
confidence: 99%